Determinants of Tax Revenue in Bihar - Priya, Shruti (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
Revenue mobilization happens to be one of the challenges for any state especially for Bihar where about 88 percent of the population is still dependent on agriculture (NCAER and NITI Ayog, 2025). A quarter century of bifurcation seems to be apt time for the analysis of the trends and determinants of revenue in the state. There are various factors that affect the revenue base of a state. The chief being the status and trend in State Gross Domestic Product, the percent of urban population, level of literacy to mention a few. A growing state income coming from secondary and tertiary sectors provides a wider tax base and hence greater tax earnings for the state. The present paper explores the relationship between Gross State Domestic Product and tax revenue collection for the state of Bihar.